Structural characterization and evaluation of mosquito-larvicidal property of silver nanoparticles synthesized from the seaweed, Turbinaria ornata (Turner) J. Agardh 1848. (4th July 2017) - Deepak, Paramasivam; Sowmiya, Rajamani; Ramkumar, Rajendiran; Balasubramani, Govindasamy; Aiswarya, Dilipkumar; Perumal, Pachiappan
Abstract: The silver nanoparticles synthesized from Turbinaria ornata (To-AgNPs) showed spherical with crystalline nature (20–32 nm) was evaluated against fourth instar larvae of three mosquitoes. The maximum activity of To-AgNPs was recorded on Aedes aegypti followed by Anopheles stephensi and Culex quinquefasciatus with the following lethal concentration values (μg/ml): LC50 of 0.738, 1.134, and 1.494; and LC90 of 3.342, 17.982, and 22.475, respectively. The obtained respective values (μg/ml) vis-a-vis aqueous extract (To-AE) were: 2.767 and 40.577; 4.347 and 158.399, and 7.351 and 278.994. The findings revealed that To-AgNPs could form a base for the development of an eco-friendly, low-cost pesticide.